Sensitivity analysis of operational parameters on excess sludge reduction in moving bed biofilm reactor (MBBR) system upgraded to integrated fixed film activated sludge (IFAS) process based on GPS-X environment - Khudhair, Duaa Natheer (Water environment research : a research publication of the Water Environment Federation, 2025)
© 2025 Water Environment Federation.